Effect of the take-up velocity on the higher-order structure of the melt-electrospun PLLA/PDLA blend fibers - Yamamoto, M.; Nishikawa, G.; Afifi, A.M.; Lee, J.C.; Yamane, H. (The Society of Fiber Science and Technology, Japan, 2015)
The higher-order structure and the formations of SC and HC of the PLLA/PDLA blend melt-electrospun fibers collected on a rotating target were investigated. The diameter of the fiber decreased and the orientation factor increased with increasing take-up velocity. The formation of SC was promoted with decreasing fiber diameter and with increasing take-up velocity. The fiber collected on the fixed target was amorphous and did not show the molecular orientation to any particular directions indicating that the stretching of the fiber by the electrostatic force did not give much molecular orientation to the fiber. On the other hand, the stretching of the fiber by applying the mechanical taking-up gave a significant degree of the molecular orientation to the fiber direction. The crystalline orientation of HC of the annealed fiber was higher than that of SC.